Enhanced surveillance of methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia in children in the UK and Ireland. Issue 10 (1st June 2010) - Johnson, A P; Sharland, M; Goodall, C M; Blackburn, R; Kearns, A M; Gilbert, R; Lamagni, T L; Charlett, A; Ganner, M; Hill, R; Cookson, B; Livermore, D; et al.
Abstract : Objective: To determine the incidence and demographic features of methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia in children in the UK and Ireland and to characterise MRSA isolated from cases. Design: Prospective surveillance study. Setting: Children aged <16 years hospitalised with bacteraemia due to MRSA. Methods: Cases were ascertained by active surveillance involving paediatricians reporting to the British Paediatric Surveillance Unit and by routine laboratory surveillance. Patient characteristics were obtained using questionnaires sent to reporting paediatricians. MRSA isolates were characterised using molecular and phenotypic techniques including antimicrobial susceptibility testing. Results: 265 episodes of MRSA bacteraemia were ascertained, involving 252 children. The overall incidence rate was 1.1 per 100 000 child population per year (95% CI 0.9 to 1.2): 61% of the children were aged <1 year (a rate of 9.7 cases per 100 000 population per year (95% CI 8.2 to 11.4)) and 35% were <1 month. Clinical data were obtained from 115 cases. The clinical presentation varied, with fever present in only 16% of neonates compared with 72% of older children. A history of invasive procedure was common, with 32% having had intravascular lines and 13% having undergone surgery. 62% of patients for whom data were available were receiving high-dependency care (46% in SCBU/NICU and 16% in PICU). Of 93 MRSA isolates studied, 73% belonged to epidemic strains widely associated with nosocomial infection in the UK and Ireland. Conclusions: MRSA bacteraemia in children was relatively uncommon and was predominantly seen in very young children, often those receiving neonatal or paediatric intensive care. Bacteraemia predominantly involved well-documented epidemic strains of MRSA associated with nosocomial infection.